Seasonal and interannual variability of tropospheric ozone over an urban site in India: A study based on MOZAIC and CCM vertical profiles over Hyderabad. Issue 6 (28th March 2014) - Sahu, L. K.; Sheel, Varun; Kajino, M.; Deushi, M.; Gunthe, Sachin S.; Sinha, P. R.; Sauvage, B.; Thouret, Valérie; Smit, Herman G.
Abstract This study is based on the analysis of Measurement of Ozone and Water Vapor by Airbus In‐Service Aircraft (MOZAIC) data measured over Hyderabad, India during the years 2006–2008. Tropospheric profiles of O3 show clear seasonality with high and low values during the premonsoon and monsoon seasons, respectively. Analysis of back trajectory and fire count data indicates major roles for long‐range transport and biomass burning in the seasonal variation of O3. Typically, lower levels of O3 in the monsoon season were due to the flow of marine air and negligible regional biomass burning, while higher levels in other seasons were due to transport of continental air. In the upper troposphere, relatively low levels of O3 during the monsoon and postmonsoon seasons were associated with deep convection. In the free troposphere, levels of O3 also show year‐to‐year variability as the values in the premonsoon of 2006 were higher by about 30 ppbv compared to 2008. The year‐to‐year variations were mainly due to transition from El Niño (2006) to La Niña (2008). The higher and lower levels of O3 were associated with strong and weak wind shears, respectively. Typically, vertical variations of O3 were anticorrelated with the lapse rate profile. The lower O3 levels were observed in the stable layers, but higher values in the midtroposphere were caused by long‐range transport. In the PBL region, the mixing ratio of O3 shows strong dependencies on meteorological parameters. The Chemistry Climate Model (CCM2) reasonably reproduced the observed profiles of O3 except for the premonsoon season.